Glass Library :The Librarian of Crooked Lane - Book 1 - Archer, C. J. ([Place of publication not identified] : C.J. Archer, 2022)
"Librarian Sylvia Ashe knows nothing about her past, having grown up without a father and a mother who refused to discuss him. When she stumbles upon a diary that suggests she's descended from magicians, she's skeptical. After all, magicians are special, and she's just an ordinary girl who loves books. She seeks the truth from a member of the most prominent family of magicians, but she quickly learns that finding the truth won't be easy, especially when he turns out to be as artless as her, and more compelling and dangerous than books. War hero Gabe is gifted with wealth, a loving family, and an incredible amount of luck that saw him survive four harrowing years of a brutal war without injury. But not all injuries are visible. Burying himself in his work as a consultant for Scotland Yard, Gabe is going through the motions as he investigates the theft of a magician-made painting. But his life changes when he unwittingly gets Sylvia dismissed from her job and places her in danger. After securing her new employment in a library housing the world's greatest collection of books about magic, Gabe and Sylvia's lives become intwined as they work together to find both the painting and the truth about Sylvia's past before powerful people can stop them. But sometimes the past is better left buried"--
Keywords: Librarians -- Fiction; Magicians -- Fiction; Inheritance and succession -- Fiction; Art thefts -- Fiction. -- Investigation; Man-woman relationships -- Fiction; Detective and mystery fiction; Fantasy fiction